Systematic Review of Executive Function Stimulation Methods in the ADHD Population - Ramos-Galarza, Carlos (2024)
Indexed keywords SciVal Topics Metrics Funding details Abstract Background/Objectives: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by elevated motor activity, impulsivity, and attention deficit. Approximately 5% of the population suffers from this disorder. Among the key explanations of ADHD, executive functions play an important role in understanding the symptomatology present in this disorder and in determining the main treatment strategies for affected patients. We present a systematic review that seeks to identify the treatment methods developed to support executive functions in individuals with ADHD. Methods: Articles were analyzed in the SCOPUS, PUBMED, and Science Direct databases. Initially, 739 articles were found. After applying inclusion and exclusion criteria, 30 articles remained and were included in the data extraction process. Results: Among the primary treatments identified, 14 studies propose psychological training for executive functions, 9 studies recommend medication, 5 studies suggest digital interventions, and 1 study advocates for sports as beneficial for executive functions. Conclusions: The data are discussed around the need to develop new proposals to enhance the executive functions of individuals with ADHD, thereby improving their performance in educational, personal, social, and family activities impacted by this disorder.